HYBRID WORK MODELS AND THE FUTURE OF HRM: CHALLENGES, ADAPTATIONS, AND OPPORTUNITIES - Latuba, Jurtan (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The COVID-19 pandemic accelerated the adoption of a hybrid work model that combines remote work and physical presence. This model has been implemented by 74% of global companies and is preferred by 83% of employees, transforming core Human Resource Management (HRM) functions such as recruitment, training, performance management, and retention. Despite significant benefits such as recruitment efficiency, reduced training time, and increased productivity, understanding the impact of this model on the HRM function and the adaptive strategies required remains limited.This research uses a narrative review with literature analysis from 2015–2025, focusing on the five main functions of HR and supported by Strategic HRM theory, the AMO Framework, and the Ulrich HR Model. The results highlight the digitalization of recruitment processes, the adaptation of digital training, changes to results-based performance management, and the need for new strategies to improve employee engagement and retention. HR is transforming into a strategic partner that prioritizes digital competency and data analytics.In conclusion, the hybrid work model fundamentally changes the HRM function and demands holistic strategic adaptation. This research contributes to HRM theory and practice in the hybrid work era by offering guidance on technology- and work culture-based adaptation.